2018
DOI: 10.1136/esmoopen-2018-000354
|View full text |Cite
|
Sign up to set email alerts
|

Safety data from the phase III Japanese ACHIEVE trial: part of an international, prospective, planned pooled analysis of six phase III trials comparing 3 versus 6 months of oxaliplatin-based adjuvant chemotherapy for stage III colon cancer

Abstract: BackgroundThe International Duration Evaluation of Adjuvant chemotherapy project investigated whether a shorter duration of oxaliplatin-based adjuvant chemotherapy was as effective as 6 months of identical chemotherapy for resected stage III colon cancer. As part of this project, we report safety data from the Japanese ACHIEVE study (JFMC47-1202-C3).Patients and methodsACHIEVE was an open-label, multicentre trial randomising patients with stage III colon cancer to receive 3 m or 6 m of mFOLFOX6/CAPOX after sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
7
20
2
Order By: Relevance
“…Colon cancer (CC), also known as colorectal or bowel cancer, is the third most frequent malignant cancer, and more than 65 percent of CC cases are found in developed countries (Kotaka et al, ). Aging is the most critical risk factor for CC, and other risk factors for CC include obesity, smoking, drinking, lack of physical activity, inflammatory bowel diseases, and inherited genetic disorders (Board, ; Theodoratou, Timofeeva, Li, Meng, & Ioannidis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer (CC), also known as colorectal or bowel cancer, is the third most frequent malignant cancer, and more than 65 percent of CC cases are found in developed countries (Kotaka et al, ). Aging is the most critical risk factor for CC, and other risk factors for CC include obesity, smoking, drinking, lack of physical activity, inflammatory bowel diseases, and inherited genetic disorders (Board, ; Theodoratou, Timofeeva, Li, Meng, & Ioannidis, ).…”
Section: Introductionmentioning
confidence: 99%
“…These results on toxicity were reproduced in the Adjuvant Chemotherapy for colon cancer with HIgh EVidencE trial (ACHIEVE) trial by Kotaka et al 7 in this issue of ESMO Open . These authors confirmed that delivering adjuvant therapy for only 3 months reduced the incidence of key adverse events.…”
mentioning
confidence: 61%
“…Thus, a shorter duration of adjuvant CapOX therapy would be beneficial so long as efficacy is not affected. In this regard, the ACHIEVE trial confirmed that a shorter duration of oxaliplatin-based adjuvant chemotherapy resulted in a significant reduction of PSN in a Japanese population with Stage III colon cancer [30].…”
Section: Discussionmentioning
confidence: 86%